Bicarbonate uptake via an anion exchange protein is the main mechanism of inorganic carbon acquisition by the giant kelp Macrocystis pyrifera (Laminariales, Phaeophyceae) under variable pH. Issue 6 (11th November 2014) - Fernández, Pamela A.; Hurd, Catriona L.; Roleda, Michael Y.; Wernberg, T.
<x xml:space="preserve">Abstract</x> Macrocystis pyrifera is a widely distributed, highly productive, seaweed. It is known to use bicarbonate (HCO3−) from seawater in photosynthesis and the main mechanism of utilization is attributed to the external catalyzed dehydration of HCO3− by the surface‐bound enzyme carbonic anhydrase (CAext). Here, we examined other putative HCO3− uptake mechanisms in M. pyrifera under pHT 9.00 (HCO3−: CO2 = 940:1) and pHT 7.65 (HCO3−: CO2 = 51:1). Rates of photosynthesis, and internal CA (CAint) and CAext activity were measured following the application of AZ which inhibits CAext, and DIDS which inhibits a different HCO3− uptake system, via an anion exchange (AE) protein. We found that the main mechanism of HCO3− uptake by M. pyrifera is via an AE protein, regardless of the HCO3−: CO2 ratio, with CAext making little contribution. Inhibiting the AE protein led to a 55%–65% decrease in photosynthetic rates. Inhibiting both the AE protein and CAext at pHT 9.00 led to 80%–100% inhibition of photosynthesis, whereas at pHT 7.65, passive CO2 diffusion supported 33% of photosynthesis. CAint was active at pHT 7.65 and 9.00, and activity was always higher than CAext, because of its role in dehydrating HCO3− to supply CO2 to RuBisCO. Interestingly, the main mechanism of HCO3− uptake in M. pyrifera was different than that in other Laminariales studied (CAext‐catalyzed reaction) and we suggest that species‐specific knowledge of carbon uptake mechanisms is required in order to elucidate how seaweeds might respond to future changes in HCO3−:CO2 due to ocean acidification.